2012
DOI: 10.1017/s0033291712000062
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of non-affective psychosis in relation to cannabis use, other drug use and gender

Abstract: Background. Cannabis use is associated with an earlier age at onset of psychotic illness. The aim of the present study was to examine whether this association is confounded by gender or other substance use in a large cohort of patients with a non-affective psychotic disorder.Method. In 785 patients with a non-affective psychotic disorder, regression analysis was used to investigate the independent effects of gender, cannabis use and other drug use on age at onset of first psychosis.Results. Age at onset was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…Indeed, the Cox regression analysis, adjusted for gender, indicates that subjects with a history of cannabis use have a 39% increased hazard of experiencing a psychosis onset at any given time compared to never users of the same gender and age. Thus, in line with a Dutch study, 28 our data suggest an independent effect of both gender and cannabis use on AOP and identify male cannabis users as the group with the earliest AOP. Moreover, consistent with evidence that the magnitude of the risk is dependent upon the potency of the cannabis used and the frequency of use, 12,13 we found a differential effect of pattern of cannabis use on AOP.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the Cox regression analysis, adjusted for gender, indicates that subjects with a history of cannabis use have a 39% increased hazard of experiencing a psychosis onset at any given time compared to never users of the same gender and age. Thus, in line with a Dutch study, 28 our data suggest an independent effect of both gender and cannabis use on AOP and identify male cannabis users as the group with the earliest AOP. Moreover, consistent with evidence that the magnitude of the risk is dependent upon the potency of the cannabis used and the frequency of use, 12,13 we found a differential effect of pattern of cannabis use on AOP.…”
Section: Discussionsupporting
confidence: 92%
“…Men have been shown to have an earlier onset of schizophrenia than women [167, 168], and age of onset of in cannabis users is shown to be earlier than non-users [168, 169]. Though cannabis use was shown to be more prevalent among men with schizophrenia relative to women [170], female cannabis users are reported to be at higher risk of early onset of psychosis compared to male users [171].…”
Section: Sex Differences In Cannabis Use Comorbidity With Psychiatricmentioning
confidence: 99%
“…In a systematic review, it has been reported that cannabis users who also smoke tobacco are more dependent on cannabis, have more psychosocial problems, and have poorer cessation outcomes than those who use cannabis but not tobacco (Peters, Budney, & Carroll, 2012); and a separate review concluded that some mechanisms linking cannabis and tobacco are distinct from those contributing to co-occurring drug use in general (Agrawal, Budney, & Lynskey, 2012). Finally, there has been a surge of research in recent years that has demonstrated not only robust links between cannabis use and risk of subsequent psychosis, but also a possible causal role of cannabis use in the development of psychosis among a subset of vulnerable individuals (Barkus & Murray, 2010;Dekker et al, 2012;Di Forti et al, 2012;Galvez-Buccollini et al, 2012;Griffith-Lendering, Wigman, van Leeuwen, Huijbregts, & Huizink, 2013;Large, Sharma, Compton, Slade, & Nielsson, 2011;Manrique-Garcia et al, 2012;Moore et al, 2007;Tosato et al, 2013).…”
Section: June 2007 Using International Classification Of Diseases (Imentioning
confidence: 99%